2011
DOI: 10.1021/ac201498a
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Inhibition of Heparinase by Persulfonated Glycosaminoglycans: A Tool to Detect Heparin Contamination

Abstract: Heparin and the low molecular weight heparins are extensively used as medicinal products to prevent and treat the formation of venous and arterial thrombi. In early 2008, administration of some heparin lots was associated with the advent of severe adverse effects, indicative of an anaphylactoid-like response. Application of orthogonal analytical tools enabled detection and identification of the contaminant as oversulfated chondroitin sulfate (OSCS) was reported in our earlier report. Herein, we investigate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
(105 reference statements)
1
10
1
Order By: Relevance
“…In previous work we have shown that the inhibition of heparinase by OSCS is irreversible, since addition of heparin does not dislodge the inhibitor [21]. Similar results were also found by other authors [22].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In previous work we have shown that the inhibition of heparinase by OSCS is irreversible, since addition of heparin does not dislodge the inhibitor [21]. Similar results were also found by other authors [22].…”
Section: Resultssupporting
confidence: 88%
“…The differences observed in the figure are related to the fact that bovine heparin is a better substrate for heparitinase II compared to porcine heparin. The results from other authors, performing kinetics studies of heparitinase II in the presence of OSCS indicate that the enzyme is inhibited [22]. These apparent discrepancies may be related to the types of experiments performed by the groups.…”
Section: Resultsmentioning
confidence: 97%
“…Other ingenious methods for detection and quantification of OSCS in heparin include a heparinase inhibition assay (Aich et al, 2011), a convenient disposable strip-type electrochemical polyanion sensor (Kang et al, 2011), pyrolysis MS (Nemes et al, 2013), and spectropolarimetry (Chmielewski et al, 2011;Stanley et al, 2011).…”
Section: F Detection Of Contaminants and Impuritiesmentioning
confidence: 99%
“…However, the C5 proton of 3-O-sulfonated uronic acid is still further away from the critical H151 amino acid residue of the enzyme, prohibiting the cleavage of OSCS, which leads to the enzyme inhibition. 18 In this technical report, we discuss the synthesis and application of the gold-heparin dye nanosensor in assessing OSCS levels in pharmaceutical heparin lots for safeguarding the complex global supply chain.…”
Section: Introductionmentioning
confidence: 99%